Pandemic Covid 19, Social Psychology, and Pregnancy: Related-ness and Analysis - Fayola Issalillah (Journal of Social Science Studies (JOS3), 2021)
The Covid-19 pandemic is one of the sixth health emergencies of international concern. The government has implemented several adjustments to people's behavior, such as national and regional lockdowns, social distancing, and restrictions on mobility to reduce the spread of this virus. However, this action raises various adverse social psychological problems, especially for pregnant women as a risk factor for Covid-19. This study aims to determine the impact of the Covid-19 pandemic on the social psychology of pregnant women. This study uses a method. The result shows the Covid-19 pandemic has an impact on the psychology of pregnant women, both interpersonal and interpersonal. This certainly allows bad things to happen to pregnant women, such as anxiety, depression and post traumatic stress disorder (PTSD), which leads to complications during pregnancy. Several treatments with a social psychological approach can be done to prevent the impact of the pandemic on the psychosocial impact of pregnant women.